Retroviral Vectors in Gene Therapy: Mechanism of Integration, Successes in Gene Therapy Trials, Emerging Problems and Potential Solutions - Salem, Ahmed F.; Smith, Johanna; Lisanti, Michael; Daniel, Rene (IntechOpen, 2011)
None